Obstetric Outcomes of Fetal Malpresentation and Malpositions - Khan, Saira; Anbreen, Fauzia (Indus Journal of Bioscience Research, 2025)
Background: Fetal malpresentation and malposition are leading contributors to the high rates of adverse obstetric outcomes such as obstructed labor, postpartum hemorrhage, and cesarean deliveries. Accurate data on these outcomes is critical in the improvement of maternal and neonatal care, particularly in resource-limited settings. Methodology: This descriptive study aimed to determine the frequency of obstetric outcomes in patients with fetal malpresentation and malposition. It was conducted at the Department of Obstetrics and Gynecology, DHQ Hospital, Dera Ismail Khan, over a period of five months, from August 2024 to December 2024. A sample size of 340 women aged 18 to 40 years with singleton pregnancy and ultrasound confirmation of fetal malpresentation or malposition. The excluded conditions are: stillbirth; placenta previa; uterine rupture, or any other major complication. Data of outcomes concerning obstetric cases were collected in relation to obstructed labor, postpartum hemorrhage, perineal tears, modes of delivery. The data analyzed were using SPSS version 26. Results: The mean age of participants was 28.09 ± 5.20 years, with a mean gestational age of 36.72 ± 2.95 weeks. Malpresentation was observed in 62.4% of cases, while 37.6% had malposition. Obstetric outcomes included obstructed labor in 12.9%, postpartum hemorrhage in 15.9%, and perineal tears in 4.7% of cases. Delivery modes comprised 6.5% vaginal deliveries, 74.4% emergency cesarean sections, and 15.9% elective cesarean sections. Malposition was significantly associated with perineal tears (p = 0.036). Conclusion: Fetal malpresentation and malposition are associated with a high prevalence of adverse obstetric outcomes, particularly emergency cesarean sections and obstructed labor.